Archeohandi: protocol for a national disabilities database in archaeology in France - Rozenn Colleter; Valérie Delattre; Cyrille Le Forestier; Alex Baiet; Philippe Blanchard; Fanny Chenal; Anne-Sophie Coupey; Stéphanie Desbrosse-Degobertière; Sylvie Duchesne; Cécile Durin; Jean-Luc Gisclon; Noémie Gryspeirt; et al. (Virtual Archaeology Review)
The archaeology of disability is a relatively recent and little-known approach in France. While the study of palaeopathology now goes hand in hand with funerary archaeology and osteoarchaeology, the French study of disabilities and disabling pathologies remains marginal and unevenly treated, depending on location, chronology and researcher’s interest. This paper focuses on highlighting the compatibility between this new research area, the obligations of osteoarchaeology, and the benefits of developing a national, diachronic, and interdisciplinary study. A database is designed within an interpretive, consensual framework, that can be adapted to overcome limitations and promote open-minded research on the care of the disabled in their own communities. A preliminary category selection of disabling pathologies has been made. These are trepanation, completely edentulous and/or compensating denture, neuronal impairment, severe scoliosis, Paget's disease, Diffuse Idiopathic Skeletal Hyperostosis (DISH), rickets, dwarfism, infectious diseases, unreduced fracture, amputation, severe degenerative disease and others. This list has been critically reviewed by experts in the field; it will evolve in a somewhat Darwinian fashion. Our database is hosted on the Huma-Num platform, with a management interface and quick access based on multiple tabs. The data includes information about archaeological operations, subjects, and pathologies; it is complemented by pictorial data stored on the Nakala platform. The development involved creating a prototype using HTML, CSS, JavaScript, SQL, and PHP, with features to display, add, modify, and delete operations and subjects. Enhancements have been made, including search optimization, charts, and the ability to export data in CSV format. The database, whose administrative interface can be accessed at archeohandi.huma-num.fr, contains so far 211 existing operations with a total of 1232 registered subjects spread throughout metropolitan France. These initial data reveal numerous research perspectives in osteoarchaeology that can be combined with other research topics, such as virtual reality.